Dusting off the Social Identity Approach to Overcome Barriers From Climate Change Communication to Pro-Environmental Behaviours - Tuva Bræin; Freja N. Rohde Monney; Tina A.G. Venema (University of Zurich, IKMZ - Department of Communication and Media Research, 2024)
For climate change communication to result in pro-environmental behaviours that could mitigate the negative consequences of climate change on human and planetary health, a thorough understanding of what prevents the intended effects is needed. In this article, we propose an additional perspective to Per Espen Stoknes' theoretical model of the five barriers to climate action. We suggest that the innermost barrier, Identity, should be conceptualized as social identity instead of cultural identity, and that the model should be updated with the theoretical premises of the social identity approach. Specifically, we propose that climate communication can be unsuccessful 1) due to identification with social identities that are incompatible with pro-environmental behaviour, 2) by emphasising an intergroup conflict and 3) by creating an intra-personal conflict. Possibly, this offers theoretical depth to understanding how an individual's identity prevents the effects of climate communication and the adoption of pro-environmental behaviours.